Academic Supervision Based on Coaching and Mentoring as an Effort to Improve Teacher Competence in Elementary Schools - Hidayatun Nur; Mamik Norsetiani; Yunita Damayanti; Siti Aniqoh Shofwani (Pena Anda: Jurnal Pendidikan Sekolah Dasar, 2025)
Improving teacher competence is an urgent and important need to support the quality of learning in schools and the quality of education in Indonesia in the current era of globalization. The purpose of this study is to explore how academic supervision based on coaching and mentoring can contribute to improving teacher competence at SD Negeri 1 Karangrowo Undaan Kudus. The research method applied is qualitative descriptive research with the Elementary School Action Research (PTS) approach. Data collection techniques applied include observation, interviews and documentation. The data that has been collected is then analyzed using the Miles and Huberman interactive model, namely: (1) Data Reduction; (2) Data Verification; (3) Data Display and (4) Drawing Conclusions. The data validity test in this study uses triangulation, where researchers collect data while testing its credibility. Research Results Coaching and mentoring based on academic supervision can improve teacher competence at SD Negeri 1 Karangrowo Undaan Kudus. The application of academic supervision based on coaching and mentoring is effective in building a strong partnership between the principal and teachers. This program has a positive impact on the overall education ecosystem which ultimately encourages the growth of intrinsic teacher motivation such as increasing teacher competence, teacher self-confidence, and contributing to improvements in the quality of learning.